RETRACTED : The Effect of Service Quality, Price and Complaint Handling on Customer Satisfaction of ibis budget Daan Mogot hotel - Gusna Welly; Resti Hardini; Kumba Digdowiseiso (Journal of Social Science, 2024)
This study aimed to analyze the effect of service quality, price and handling of complaints on consumer satisfaction Ibis Budget Hotel. The method used in this research is quantitative descriptive with population in this study is consumer in ibis budget hotel. There are four variables studied in this research is Service Quality (X1), Price (X2) and Handling of Complaints as independent variables and Consumer Satisfaction (Y) as the related variables. The sample used in the study in 100 respondents. The data in this study using primary data by distributing questionnaires with multiple linear regression method that processed the use of SPSS 17.0 software. the results of research based on multiple linear regression analysis showed that the Service Quality (X1), Price (X2) and Handling of Complaints positive and significant impact on the consumer Satisfaction (Y).